The continuing legacy of John Maynard Keynes - L. Randall Wray (Levy Economics Institute of Bard College, 2007)
This working paper examines the legacy of Keynes's General Theory of Employment, Interest, and Money (1936) on the occasion of the 70th anniversary of its publication and the 60th anniversary of Keynes's death. The paper incorporates some of the latest research by prominent followers of Keynes, presented at the 9th International Post Keynesian Conference in September 2006.
Keywords: B3; B5; E12; 330; Keynes's Legacy; Keynesian Theory; Keynesian Policy